Keberadaan Total Quality Management Dalam Lembaga Pendidikan (Antara Prinsip Implementasi Dan Pilar TQM Dalam Pendidikan) - Miftakhul Munir (Realita: Jurnal Penelitian dan Kebudayaan Islam, 2018)
In order to produce a quality education quality, the world of education is necessary to implement the concept of Total Quality Management (History Quality Total) which in history has successfully delivered the business world or the business world in creating the best production quality that can even exceed customer satisfaction standards (customer) -his. The problem that the writer peeled in this article is: What is the Understanding of TQM Implementation and Its Existence in Educational Institution? How are the Pillars and Principles of TQM Implementation in Education Institutions? How are the TQM Implementation Steps in Education Institutions? And How Failure in TQM Implementation? This article can be concluded as follows: 1) Total Quality Management (TQM) or commonly referred to in Indonesia as a Total Quality Management (MMT) is very necessary to be adopted, applied and developed in the world of education, educational institutions, especially schools. 2) This TQM concept will not achieve its goal if the principles in TQM itself are not firmly held. 3) Implemantation of TQM in the education and business world has an essential difference. It can be seen from the product and its purpose. Products at school are graduates who are ready with science plus practice and a good attitude or attitude to the graduates. 4) Failure in TQM implentation can be summed up entirely because of inconsistencies of some or all of the quality components present in the school.